PF.29 Should We Reconsider the Elective Mode of Delivery in Gastroschisis?. (26th April 2013) - Mullers, S; Flood, K; Burke, N; Geary, M; Barry, C; Breathnach, FM; Malone, FD
Abstract : The recommended mode of delivery for the fetus with an abdominal wall defect is controversial, with no evidence to support caesarean delivery other than for routine obstetric indications. We sought to review mode of delivery in cases of prenatally diagnosed gastrochisis in our centre. This was a retrospective cohort study of prenatally diagnosed fetal gastroschisis cases in the Rotunda Hospital over a fourteen year period. Cases were identified from the Fetal Assessment Unit database. We identified 35 cases fetal gastroschisis cases during the study period. The average age of mothers was 22.5 years. The median gestation at delivery was 35 + 4 with an average birthweight of 1.97 kg. An elective caesarean section was performed in 13.3% (n = 4) cases. Vaginal delivery was the intended mode of delivery for the remaining cases (n = 26) however 54% resulted in an emergency caesarean delivery with nonreassuring CTG cited as the most common indication (64%, 9/14). Of these, 50% (7/14) were performed outside of normal working hours. Although the numbers in our cohort are relatively small, we found a significantly high rate of caearean delivery in young women with pregnancies complicated by gastroschisis. The high proportion of cases with nonreassuring fetal testing during labour resulted in a higher than expected number of emergency deliveries which were performed outside normal working hours. Our findings suggest that re-evaluation of the optimal mode of delivery in this cohort may be warranted.